DEVELOPMENT OF A VISIBLE SPECTROPHOTOMETRIC METHOD FOR THE QUANTITATIVE DETERMINATION OF METANIL YELLOW IN DIFFERENT FOOD SAMPLES. - PARTHA PRATIM NATH; KAUSHIK SARKAR; PANCHALI TARAFDER; GOUTAM PAUL (International Journal of Pharma and Bio Sciences, 2013)
The purpose of the investigation was to develop a simple spectrophotometric method for the determination of percentage level of occurrence of metanil yellow, a non permitted synthetic food color. This method was based on the reaction between metanil yellow and hydrochloric acid (under specific experimental conditions) to produce a color complex with an absorbance maximum of 450 nm. The complex obeyed Beer’s law in 2 μg mL-1- 20 μg mL-1 concentration range and exhibited a good correlation coefficient (R2), a satisfactory Sandell’s sensitivity and of recovery (R %) close to 100 %. The use of the described simple and sensitive spectrophotometric method for the routine quality control analysis of food stuffs by determination of metanil yellow overcomes any barriers to food safety evaluation occasioned by the need for costly analytical equipment. The statistical data support the accuracy and precision of the proposed method.